Bliciousseries Ordering and Sales Management System - TEO AH HING@TIEO AH HING, LILY NATASHA; AMAN, HANNNANI (Applied Information Technology And Computer Science, 2026)
Bliciousseries, a cookie brand company based in Seri Medan, Johor, faces operational challenges in managing orders and payments manually, particularly during high-demand seasons such as Hari Raya Aidilfitri. The business currently relies on WhatsApp to communicate with agents, resulting in delays, miscommunication, and errors. This project presents the development of a web-based Ordering and Sales Management System using Python to streamline order processing, payment verification, and sales tracking for both agents and customers. The system focuses on enhancing agent-based order management with direct customer ordering capabilities and also referral and commission module. System testing with users from all roles confirmed that all relevant features functioned correctly and met user expectations. The system significantly improves efficiency by reducing manual errors, speeding up order processing, and enabling real-time sales tracking. Future enhancements will focus on integrating e-wallet payments, implementing an agent tier system, and developing a mobile-friendly version.